2021
DOI: 10.1101/2021.06.22.449496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Witnessing the structural evolution of an RNA enzyme

Abstract: An RNA polymerase ribozyme that has been the subject of extensive directed evolution efforts has attained the ability to synthesize complex functional RNAs, including a full-length copy of its own evolutionary ancestor. During the course of evolution, the catalytic core of the ribozyme has undergone a major structural rearrangement, resulting in a novel tertiary structural element that lies in close proximity to the active site. Through a combination of site-directed mutagenesis, structural probing, and deep s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This approach has proven to be powerful in optimizing the activity of a homochiral RNA polymerase ribozyme. 5,24,25 By comparison, the cross-chiral polymerase is a relatively young enzyme that has not had yet the benefit of extensive evolutionary optimization.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This approach has proven to be powerful in optimizing the activity of a homochiral RNA polymerase ribozyme. 5,24,25 By comparison, the cross-chiral polymerase is a relatively young enzyme that has not had yet the benefit of extensive evolutionary optimization.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…effects on their fitness. Contrasting evidence can also be found in other experimental studies that demonstrated that artificial evolution can be used to engineer a ribozyme that adopts a new structure while retaining its function 21 , or that acquires a new function 22,23 .…”
mentioning
confidence: 91%
“…Thus the t1 domain and its KL interactions may together serve to hold J1/3 in this out-stretched conformation, as a longer or untethered single-stranded templatebinding strand would likely be more dynamic and adopt a variety of conformations, increasing the entropic cost of template interaction. Analysis of the evolution of the related 52-2 polymerase ribozyme (which used NTPs as substrates) 7 suggest the emergence of a pseudoknot structure involving P7 and the J1/3 equivalent, which . CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Evolution Of a Mutualistic Heterodimermentioning
confidence: 99%
“…RNA catalysts (ribozymes) occupy central structural and catalytic roles in the function of modern cells including tRNA processing (RNaseP), mRNA splicing (spliceosome, group I / II self-splicing introns) and translation (ribosome peptidyl transferase center) 15 . In addition, a much wider variety of ribozyme activities not found in nature has been discovered by in vitro evolution, including polymerase ribozymes (PR) that are capable of synthesizing a complementary strand on an RNA template 3-7,11 . The capacity for RNA-catalyzed RNA-templated synthesis and replication is widely believed to have been a central pillar of the emergence of life’s first genetic system and even life itself.…”
Section: Cryo-em Structure Of Optimized Tpr Heterodimermentioning
confidence: 99%
See 1 more Smart Citation